PENYULUHAN HUKUM TENTANG KORBAN TIDAK MELAKUKAN PENCATATAN PERKAWINAN PADA WAKTU PERNIKAHAN MENURUT PERATURAN MENTERI AGAMA NO. 19 TAHUN 2018 DI KECAMATAN BOGOR UTARA - Sri Hartini; Latifah Ratnawati; Ande Aditya Iman Ferrary; Ady Iman Purwoto (JPMUJ, 2025)
Indonesia is a state of law, which must be implemented by all parties, both society and government. The definition of law is: Regulations regarding human behavior in social interactions. Law Number 1 of 1974 concerning Marriage. In this Law, the state considers a marriage to be valid if the marriage is registered as stated in Article 1 paragraph (2) which states: expressly when registering the marriage. The purpose of marriage is: 1) to obtain happiness and peace while building a family, 2) regeneration of humanity (reproduction) or obtaining offspring, 3) fulfillment of biological needs, 4) maintaining honor. 5) for worship/following the sunnah of the prophet. A valid marriage means there is a prospective husband and wife, a guardian for the marriage, there are witnesses to the marriage, and there is an agreement and consent, according to Article 14 of the 1991 Compilation of Islamic Law, for those who are Muslim.